Analysis of False-negative Findings of the Incomparable Accuracy and Swiftness of Flow Cytometric Diagnosis of Primary Central Nervous System Lymphoma - Hayato TAKEUCHI; Tohru INABA; Yukiko SHISHIDO-HARA; Taku TSUKAMOTO; Shinsuke MIZUTANI; Takanari OKAMOTO; Seisuke TANIGAWA; Takumi YAMANAKA; Yoshinobu TAKAHASHI; Eiichi KONISHI; Junya KURODA; Naoya HASHIMOTO (Neurologia Medico-Chirurgica, 2023)
Primary central nervous system lymphoma (PCNSL), a relatively rare brain tumor, bears a dire prognosis. On occasion, the rapid progression of the tumor makes immediate diagnosis and initiation of therapy imperative. To achieve swift diagnosis, we adopt flow cytometry (FCM) in addition to conventional histopathology. This study aimed to reveal the utility of FCM diagnosis for PCNSL and the cause of false-negative results of FCM diagnosis. We investigated 33 patients with suspected PCNSL on neuroradiological findings and received both FCM and histological diagnosis. The patients' electronic medical records were investigated, and histological findings, results of FCM, and other clinical data were evaluated. Overall, 27 patients (14 males and 13 females) were diagnosed with PCNSL by histological confirmation. The median age at diagnosis was 68 years. FCM analysis showed lymphoma pattern in 24 cases; however, FCM results did not show lymphoma pattern (sensitivity: 88.9%, specificity: 100%) in the other three lymphoma cases (FCM discordant: FCM-D) and six nonlymphomatous tumor cases. Analysis of FCM-D cases showed the infiltration of T lymphocytes or astrocytes into the tumor tissue, indicating tumor microenvironmental reaction; it is assumed that these reactions deceived FCM diagnosis. The survival of FCM-D patients was superior to FCM concordant counterpart, although the difference was not significant (p = 0.459). The diagnosis of PCNSL by FCM is rapid and highly reliable. Some FCM-D cases are PCNSLs with strong tumor microenvironmental reactions.